14-3-3σ Regulates β-Catenin-Mediated Mouse Embryonic Stem Cell Proliferation by Sequestering GSK-3β - Chang, Tzu-Ching; Liu, Chia-Chia; Hsing, En-Wei; Liang, Shu-Man; Chi, Ya-Hui; Sung, Li-Ying; Lin, Shau-Ping; Shen, Tang-Long; Ko, Bor-Sheng; Yen, B. Linju; Yet, Shaw-Fang; Wu, Kenneth K.; et al. (PLOS ONE, 2012)
Background Pluripotent embryonic stem cells are considered to be an unlimited cell source for tissue regeneration and cell-based therapy. Investigating the molecular mechanism underlying the regulation of embryonic stem cell expansion is thus important. 14-3-3 proteins are implicated in controlling cell division, signaling transduction and survival by interacting with various regulatory proteins. However, the function of 14-3-3 in embryonic stem cell proliferation remains unclear. Methodology and Principal Findings In this study, we show that all seven 14-3-3 isoforms were detected in mouse embryonic stem cells. Retinoid acid suppressed selectively the expression of 14-3-3σ isoform. Knockdown of 14-3-3σ with siRNA reduced embryonic stem cell proliferation, while only 14-3-3σ transfection increased cell growth and partially rescued retinoid acid-induced growth arrest. Since the growth-enhancing action of 14-3-3σ was abrogated by β-catenin knockdown, we investigated the influence of 14-3-3σ overexpression on β-catenin/GSK-3β. 14-3-3σ bound GSK-3β and increased GSK-3β phosphorylation in a PI-3K/Akt-dependent manner. It disrupted β-catenin binding by the multiprotein destruction complex. 14-3-3σ overexpression attenuated β-catenin phosphorylation and rescued the decline of β-catenin induced by retinoid acid. Furthermore, 14-3-3σ enhanced Wnt3a-induced β-catenin level and GSK-3β phosphorylation. DKK, an inhibitor of Wnt signaling, abolished Wnt3a-induced effect but did not interfere GSK-3β/14-3-3σ binding. Significance Our findings show for the first time that 14-3-3σ plays an important role in regulating mouse embryonic stem cell proliferation by binding and sequestering phosphorylated GSK-3β and enhancing Wnt-signaled GSK-3β inactivation. 14-3-3σ is a novel target for embryonic stem cell expansion.